Recording Culture : Powwow Music and the Aboriginal Recording Industry on the Northern Plains - Scales, Christopher A. (Christopher Alton), 1966- (Book collections on Project MUSE., 2012)
Drawing on his ethnographic research at powwow grounds and in recording studios, Christopher A. Scales examines the ways that powwow drum groups have utilized recording technology in the late twentieth and early twenty-first centuries, the unique aesthetic principles of recorded powwow music, and the relationships between drum groups and the Native music labels and recording studios.